Rediseño del plan de seguridad y salud en el trabajo de la empresa contratista MV Servicios S.R.L. para la disminución de desviaciones - Cornejo Tejada, Jackeline Lisset (2019)
This work is called “HEALTH AND SAFETY PLAN IN THE WORK OF THE COMPANY CONTRATISTA MV SERVICIOS S.R.L. FOR THE DECREASE OF DEVIATIONS ”, describes the methodology to follow to redesign a safety and health plan at work, which can be applied in similar companies. The company MV Servicios S.R.L. evidence in most of its activities noncompliance with procedures, which exposes the health and physical integrity of its collaborators. The aforementioned is reflected in the 2017 index of reports, where a high level is observed from April to May. For this reason, several evaluations were carried out on the company MV Servicios S.R.L., in the area of occupational safety and health, baseline review and thorough analysis of the most common indicators of noncompliance with work. Starting up the redesign of the occupational health and safety plan, a significant improvement of p = 0.034 would be seen in the first 6 months. Thus, the redesign of the proposed occupational health and safety plan would have a positive effect on the rate of noncompliance with procedures of the company MV Servicios S.R.L